2010
DOI: 10.1159/000322054
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Receptor-Related Duplicons Mediate a Microdeletion at 11q13.2q13.4 Associated with a Syndromic Phenotype

Abstract: By array-CGH, we identified a cryptic deletion of about 3.4 Mb involving the chromosomal region 11q13.2q13.4 in a child with speech and developmental delay. Highly homologous segmental duplications related to the well-known olfactory receptor (OR)-containing clusters at 8p and 4p are located at the breakpoints of the imbalance and may be involved in its occurrence. Although these structural features are known to promote recurrent chromosomal rearrangements and previous studies had included the 11q13.2q13.4 del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
4
28
0
Order By: Relevance
“…Specifically, cases 6319-3 and AU038-3 had mild axial hypotonia, oral dyspraxia and minor signs or cerebellar dysfunction (including dysmetry and dysdiadochokinesis). These clinical signs are unspecific, but were also reported in patients with ASD with more complex chromosomal rearrangements encompassing SHANK2 [33]. The individual carrying the de novo truncating mutation R841X (SK 0441-003) had a normal IQ and diagnosed with ASD without any developmental delays or dysmorphic features.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, cases 6319-3 and AU038-3 had mild axial hypotonia, oral dyspraxia and minor signs or cerebellar dysfunction (including dysmetry and dysdiadochokinesis). These clinical signs are unspecific, but were also reported in patients with ASD with more complex chromosomal rearrangements encompassing SHANK2 [33]. The individual carrying the de novo truncating mutation R841X (SK 0441-003) had a normal IQ and diagnosed with ASD without any developmental delays or dysmorphic features.…”
Section: Resultsmentioning
confidence: 99%
“…A group of seven patients with ASD and ID (one of them presenting with ID only) were also carriers of rare nonsynonymous mutations predicted as deleterious, but inherited from an unaffected parent. Five independent studies then reported additional de novo heterozygous SHANK2 deletions in patients with ASD, speech, and developmental delay, and moderate ID (Pinto et al, ; Wischmeijer et al, ; Leblond et al, ; Schluth‐Bolard et al, ; Chilian et al, ). Leblond et al also observed an enrichment of mutations affecting conserved amino acids and altering synapse density in patients with ASD (Leblond et al, ).…”
Section: Shank and Autism Spectrum Disordersmentioning
confidence: 99%
“…Patient 2389 carried a smaller, completely overlapping deletion spanning from 68.072 to 70.307 Mb and had congenital deafness. Patient 251808 had a much smaller deletion between 67.644 and 68.044 Mb and presented clinical features including low-set ears, down-slanting palpebral fissures, speech delay, and mental retardation14).…”
Section: Discussionmentioning
confidence: 99%
“…Wischmeijer et al14) reported the identification of a cryptic interstitial deletion (3.4 Mb) in chromosome 11q13.2-q13.4 that spans from 67.525 to 70.964 Mb in a child. The child was diagnosed with developmental delay, severe speech delay, moderate/severe mental retardation, and some dysmorphic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation